Analysis of Business Strategy of Ayang Beib Steak Cafe in Facing Market Competition During the Covid-19 Pandemic - Pebiyara, Anisa; Appin, Appin (International Journal of Social Science, Education, Communication and Economics, 2024)
In the contemporary global market, businesses encounter intense competition, particularly within the culinary sector, driven by rapid technological advancements and economic growth. To secure long-term competitive advantages, companies must strategically position their products or services in consumers' minds through effective advertising and innovative strategies. Ayang Beib Steak Cafe, established in 2018 and located at Jl. Cik Ditiro Ruko Wisma Mas (next to Kosasih Kemiling) in Bandar Lampung, Indonesia, benefits from a strategic location on one of the city's busiest streets, surrounded by numerous culinary establishments. During the COVID-19 pandemic, Ayang Beib Steak Cafe adapted to the challenging market conditions by maintaining a dedicated team of five staff members focused on delivering excellent customer service. This study employs the Analytic Hierarchy Process (AHP) to analyze the business strategies implemented by Ayang Beib Steak Cafe to navigate market competition during the pandemic. The research identifies key internal and external factors influencing sales growth, including human resource coordination, menu diversification, outlet modernization, promotional activities, competitive conditions, consumer taste trends, and economic fluctuations. The findings suggest that modernizing outlet services and developing new menu items are the most prioritized strategies for enhancing sales and sustaining competitive advantage. Additionally, word-of-mouth and holiday promotions play significant roles in attracting and retaining customers. This comprehensive analysis provides actionable insights for Ayang Beib Steak Cafe and similar businesses aiming to thrive in a highly competitive and volatile market environment.